Geochemistry of Dadeldhura granite and its mineral potential - Kaphle, K. P. (Journal of Nepal Geological Society, 1991)
Dadeldhura granite is a cordierite bearing two mica granite. It is S-type, leucocratic and rich in silica, alumina and potash and slightly low in soda. In this granite a remarkable evolutionary trend is marked by the general increase in SiO2, Al2O3 , K2O , Na2O , P2O5, Rb, Nb and depletion of CaO, MgO, Fe2O3, TiO2, Ba, Sr, Zr, Zn and V etc. towards later phase. Mineral chemistry of biotite and feldspar and plot of chemical data on variation diagrams and triangular diagrams show a moderate to fairly strong differentiation trend from (i) granite gneiss (GGN), (ii) biotite granite (BGR) to (iii) muscovite granite (MGR) and (iv) aplitic tourmaline granite (TGR). Many physical, mineralogical and chemical characteristics of Dadeldhura granite resemble with world's average tin granite.